Monogenic causes of familial short stature - Plachy, Lukas; Dusatkova, Petra; Amaratunga, Shenali Anne; Neuman, Vit; Sumnik, Zdenek; Lebl, Jan; Pruhova, Stepanka (Frontiers in Endocrinology, 2024)
Genetic factors play a crucial role in determining human height. Short stature commonly affects multiple family members and therefore, familial short stature (FSS) represents a significant proportion of growth disorders. Traditionally, FSS was considered a benign polygenic condition representing a subcategory of idiopathic short stature (ISS). However, advancements in genetic research have revealed that FSS can also be monogenic, inherited in an autosomal dominant manner and can result from different mechanisms including primary growth plate disorders, growth hormone deficiency/insensitivity or by the disruption of fundamental intracellular pathways. These discoveries have highlighted a broader phenotypic spectrum for monogenic forms of short stature, which may exhibit mild manifestations indistinguishable from ISS. Given the overlapping features and the difficulty in differentiating polygenic from monogenic FSS without genetic testing, some researchers redefine FSS as a descriptive term that encompasses any familial occurrence of short stature, regardless of the underlying cause. This shift emphasizes the complexity of diagnosing and managing short stature within families, reflecting the diverse genetic landscape that influences human growth.